PESANTREN BETWEEN GLOBALIZATION AND POLITIZATION: Maduranese Pesantren After the Fall of New Order (1998-2007) - Fathol Haliq (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
After the fall of the Soeharto regime, there has been political euphoria and paradoxical strategies, between populist idealism and political pragmatism. Political pragmatism leaves acute problems in the world of pesantren. Culture-shock, the unpreparedness of pesantren leadership transformation led to a number of interesting strategies from the elders to give the mandate to the young keyae. In this context, there is a tug of war between change and status quo, idealism and educational pragmatism, so that the globalization agenda is not answered anticipatively and progressively. The strategy carried out by pesantren seems unsustainable, broken, pragmatic, and only answers a momentary agenda. On the other hand, pesantrens answer international problems - problems of human rights, humanity, poverty, environment, and global political economy - with steps that are typical of pesantrens, namely